CHARACTERIZING THE HEIGHT PROFILE OF THE FLUX OF WIND-ERODED SEDIMENT - Dong Zh.; Qian G. (My University, 2007)
Wind erosion causes severe environmental problems, such as aeolian desertification and dust storms, in arid and semiarid regions. Reliable prediction of the height profile of the wind-eroded sediment flux is crucial for estimation of transport rates, verification of computer models, understanding of particle-modified wind flows, and control of drifting sand. This study defined the basic height profile for the flux of wind-eroded sediment and the coefficients that characterize its equation. Nine grain-size populations of natural sand at different wind velocities were tested in a wind tunnel to measure the flux of sediment at different heights. The resulting flux profiles resemble a golf club with a small back-turn where the flux increases with increasing height within 20 mm above the surface. If the small back-turns are neglected, the flux profiles can be expressed by an exponential-decay function $ q_{{\text{r}}} (z) = a{\text{e}}^{{ - bz_{r} }} , $ where q r(z) is the dimensionless relative flux of sediment at height z, which follows the exponential-decay law proposed by previous researchers for aeolian saltation. Three coefficients (a creep proportion, a relative decay rate, and an average saltation height) are proposed to characterize the height profile. Coefficients a and b in the above equation represent the creep proportion and relative decay rate as a function of height, respectively. Coefficient a varies widely, depending on grain size and wind velocity, but averages 0.09. It is suggested that the grain size and wind velocity must be specified when discussing creep proportion. Coefficients a and b are nearly linearly correlated and decrease as grain size and wind velocity increase. The average saltation height (the average height sediment particles can reach) was a function of grain size and wind velocity, and was well correlated with coefficients a and b.
Keywords: WIND-ERODED FLUX; EXPONENTIAL-DECAY FUNCTION; CREEP PROPORTION; RELATIVE DECAY RATE; AVERAGE SALTATION HEIGHT